2010
DOI: 10.1093/ndt/gfq613
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing intravenous ferric carboxymaltose with oral iron for treatment of iron deficiency anaemia of non-dialysis-dependent chronic kidney disease patients

Abstract: Background. Iron deficiency is a common cause of anaemia and hyporesponsiveness to erythropoiesis-stimulating agents (ESAs) in non-dialysis-dependent chronic kidney disease (ND-CKD) patients. Current intravenous iron agents cannot be administered in a single high dose because of adverse effects. Ferric carboxymaltose, a non-dextran parenteral iron preparation, can be rapidly administered in high doses.Methods. This open-label trial randomized 255 subjects with glomerular filtration rates ≤ 45 mL/min/1.73 m2, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
140
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(160 citation statements)
references
References 32 publications
13
140
2
2
Order By: Relevance
“…This study is consistent with other studies that showed that in iron deficient hemodialysis patients randomized to oral iron or intravenous iron, only the group treated with intravenous iron had a significant increase in hemoglobin levels [9][10][11][12]. Intravenous iron preparations have very different molecular weights and side effect profiles [13], small proportions of patients given intravenous iron dextran develop a lifethreatening anaphylactic reaction, which is due to an immune-mediated reaction in patients who have dextran antibodies [14].…”
Section: Discussionsupporting
confidence: 90%
“…This study is consistent with other studies that showed that in iron deficient hemodialysis patients randomized to oral iron or intravenous iron, only the group treated with intravenous iron had a significant increase in hemoglobin levels [9][10][11][12]. Intravenous iron preparations have very different molecular weights and side effect profiles [13], small proportions of patients given intravenous iron dextran develop a lifethreatening anaphylactic reaction, which is due to an immune-mediated reaction in patients who have dextran antibodies [14].…”
Section: Discussionsupporting
confidence: 90%
“…An increase in hepcidin would be expected if oral iron therapy resulted in increased iron stores. That this did not occur in the oral iron group demonstrated an inferior increment in iron stores when compared to FCM therapy [21]. FCM also increased hemoglobin levels significantly when compared to oral iron therapy.…”
Section: Discussionmentioning
confidence: 86%
“…Efficacy and safety of FCM has been proved in many clinical trials done so far in patients with varying etiologies of anaemia like, inflammatory bowel disease chronic kidney disease congestive heart failure, heavy uterine bleeding and PPIDA. [8][9][10][11][12][13][14][15][16][17][18] FCM injection leads to Hb rise along with replenishment of iron stores in much shorter time. Also, there is better tolerability with low risk of anaphylaxis and other adverse effects.…”
Section: Introductionmentioning
confidence: 99%